Formation of ordered arrays of gold particles by nanoindentation templating. Issue 1 (22nd October 2013) - Wong, S.; Shalav, A.; Ruffell, S.; Bradby, J. E.; Field, M. R.; McCulloch, D. G.; Elliman, R. G.
Abstract Ordered arrays of gold‐rich particles, with diameters ranging from 50 nm to 180 nm, have been formed on a silicon (100) surface through pre‐patterning by nanoindentation. Indentation and gold deposition of the sample is followed by thermal processing, causing the gold to become trapped at the indentation sites. We suggest that gold trapping is via an alloying process with the underlying Si substrate where the native oxide is structurally compromised by the indentation process. The final size for a given particle is directly dependent on the size of the indentation site. It has also been demonstrated that excess gold found on the surface outside of these indentation sites can be readily removed via simple mechanical abrasion without affecting the particles within the indent. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)